THE SOUND OF STYLE AND PRONUNCIATION OF ENGLISH SPEECH - Fayzulloyeva Zilola Zafarovna,; Nusratullayeva Bahoraxon, (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Annotation: This article explores how pronunciation shapes speech styles in English through both segmental and suprasegmental phonetic features. It examines how vowels, consonants, rhythm, stress, and intonation contribute to distinctions between formal and informal speech, regional accents, and social identity. Drawing on perspectives from prominent linguists such as David Crystal, John C. Wells, Deborah Tannen, Jennifer Jenkins, William Labov, and Peter Trudgill, the paper demonstrates that phonetic variation is systematic and socially meaningful. The discussion highlights pronunciation as a dynamic resource that reflects identity, communicative intention, and social context rather than merely an indicator of accent. Understanding these phonetic patterns enhances awareness of spoken English diversity and improves communicative competence in global settings.